A escola no horizonte de jovens camponeses de uma escola família agrícola - Cristiane Benjamim de Freitas (2010)
This research was based on the experiences of schooling of countryside Young people of the Família Agricola Paulo Freire School from the Acaiaca-MG town, investigating the reasons which took these young people to enroll in the school and how they constructed their school path. It was defined as general objective to understand and analyze the experiences of schooling of country young students of Escola Família Agricola Paulo Freire/Acaiaca-MG. As specified objectives it was intended to describe and analyze the senses given to the schooling by the young country people; describe the limits, conflicts, and possibilities lived during this process; identify the choices and strategies that were constructed in the process of the young schooling; analyze the relation of these experiences in the construction of future projects or extending ofstudies and discuss the young condition in the countryside and its diversity. The investigated subjects were young students of the third grade of this school. The data collect happened through observation, individual interviews and semi-structured with 10 students, besides a pool applied to 71 young people of the school. These instruments could pick data about the social characteristics, cultural and schooling of the young students. The theoretical basement for the empirical material analyses based on works of studying areas about Brazilian Countryside, about the experiences of the Escolas Famílias Agrícolas, and the alternative pedagogy and on authors of Education Sociology, and the Youth Sociology. The analysis demonstrated that the school has multiple senses for the young people of the countryside, which results in a setting up of factors. The school constitutes for the young students a space of sociability, preparation for the work and social recognition. The senses given to the school by the young students have a connection with their schooling path, which were by the way marked by the social condition in which they lived and by the racial belonging or of genre. Through this research one can state that despite the young pe ople belong to the same social category, this is not homogeneous and they dont live the schooling experience by the same conditions. The sense of schooling for several young people was linked to their professional projects. We have noticed that for the most of the young people the creation of their projects presented the dilemma between remaining to the family social environment of origin developing some kind of work connected tothe family agriculture or migrating to the cities, going on with their studies and/or inserting themselves in some job. Facing this situation, the projects at most located on the unpredictably logic, of unsure and doubts